Historiografi Demokrasi dan Masalah Periodisasi Sejarah Indonesia Kontemporer - Lazuardi, Muhammad Fijar (Jurnal Sejarah Indonesia, 2024)
The periodization of contemporary Indonesian history is generally divided into three periods, namely the period of Revolution, the Liberal Democracy, the Guided Democracy, the New Order, and the Reformation. Periodization requires accuracy in determining the starting and ending points as well as consistency in the use of terms with historical facts. The Liberal Democracy in this case, there was inaccuracy in the terms used and the temporal scope that had been determined. By using historical methods that emphasize literature study, this research will explain, when the term “liberal democracy” began and what historiographical consequences there would be if that period began in 1950. From the research and analysis that has been carried out, parliamentary democracy is more appropriate to use as a periodization. Liberal democracy can be a concept that accompanies parliamentary democracy. Then the starting point of this period was 1945 when the Workers' Body-Central Indonesian National Committee as a legislative body was formed. The historiographic development of periodization starting in 1950 would miss the democratization process and the ideas of Indonesian actors and agencies at the beginning of independence, as well as the historical continuity between 1945 and 1959.